The Impact of the Fourth Amendment to the National Mineral and Coal Law on Regional Development: An Investment Law Perspective - Wamafma, Filep; Sasea, Enny Martha (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study examines the impact of the fourth amendment to the National Mineral and Coal Law (Minerba Law) on regional governance and its implications from an investment law perspective. Using a normative approach and qualitative analysis methods, the study identifies significant regulatory changes, particularly the centralization of mining permits, which has diminished the authority of regional governments. While this reform enhances legal certainty for investors and improves bureaucratic efficiency, it also raises concerns regarding environmental oversight, equitable distribution of economic benefits, and the protection of local community rights. The findings indicate that the reduced role of regional authorities increases the risk of uncontrolled resource exploitation and deepens social inequality. Therefore, policies that balance investment interests with socio-environmental sustainability are essential, emphasizing stronger oversight and greater regional government involvement in mining management.